1985
DOI: 10.1007/bf00735732
|View full text |Cite
|
Sign up to set email alerts
|

Short-term culture of pediatric brain tumors

Abstract: Three short-term culture systems were applied to ten pediatric brain tumors and two samples each of normal child's brain and fetal brain. Growth in monolayer occurred in nine of the ten tumors but normal child's brain also produced cellular growth in these conditions. Six of nine tumors tested also formed colonies in suspension in semisolid or liquid conditions which did not permit the growth of normal glial cells. Astrocytomas and medulloblastomas have distinctive growth patterns both in monolayer and in susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…28 Cells from human brain tumors have the ability to form multicellular spheroids after an initial enzymatic dissociation of the tumor tissue.~~ Spheroid formation has also been performed in short-term culture of biopsies from brain tumors in children. 18 The present study shows that surgically removed tissue specimens from human gliomas easily form tumor spheroids in agar overlay culture. Their morphological features and the individual growth of different spheroids have been studied, from the same patient as well as from different patients.…”
mentioning
confidence: 52%
“…28 Cells from human brain tumors have the ability to form multicellular spheroids after an initial enzymatic dissociation of the tumor tissue.~~ Spheroid formation has also been performed in short-term culture of biopsies from brain tumors in children. 18 The present study shows that surgically removed tissue specimens from human gliomas easily form tumor spheroids in agar overlay culture. Their morphological features and the individual growth of different spheroids have been studied, from the same patient as well as from different patients.…”
mentioning
confidence: 52%
“…These cells have the ability to self-renew, proliferate and differentiate, and uniquely maintain the tumor growth. Although qualitative reports of sphere formation in cultured brain tumor cells exist (Mackillop et al, 1985) and stem-like cells have been observed in brain tumor cultures (Ignatova et al, 2002), a prospectively isolated population of cancer stem cells from brain tumors had not been described until recently (Singh et al, 2003). The existence of cancer stem cells, first proven in the context of acute myeloid leukemia (AML), required sorting by surface markers to distinguish leukemic stem cells from the remaining AML cells, which had limited proliferative potential (Blair et al, 1997;Bonnet and Dick, 1997).…”
Section: Prospective Identification Of a Cancer Stem Cell From Human mentioning
confidence: 99%
“…They are believed to be a better model than monolayer cultures due to a three-dimensional structure with more in vivo-like intercellular contacts. This model was later on further improved by deriving spheroids from single cells obtained from dissociated primary glioblastoma tissue (Mackillop et al, 1985). In order to obtain an even more in vivo-like model the primary organotypic spheroids were introduced .…”
Section: Establishment and Development Of The Spheroid Modelmentioning
confidence: 99%
“…However, the three-dimensional aspect came into focus in the 1970's, where scientists started to grow tumor cells from cell lines as multicellular spheroids (Yuhas et al, 1977). Over the years the spheroid model has been improved by deriving spheroids from cells obtained from dissociated primary glioblastoma tissue (Mackillop et al, 1985) as well as by using organotypic primary spheroids derived from small tumor fragments . In general, most in vitro studies are performed with cells cultured in conventional serumcontaining medium.…”
Section: Introductionmentioning
confidence: 99%